Ultrafine polyphenylene sulfide fiber, non-woven fabric, and method for producing same

By reducing fine fiber diameter and controlling the crystallinity, preparation of excellent adhesive and decentralized polar piping benzhenylvanal fiber, solve the problem of thinning and intensity of non -woven fabrics, and realizing high -performance non -woven fabrics preparation.

CN119365642APending Publication Date: 2025-01-24TORAY INDUSTRIES INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380042171.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-08
Filing Date
2023-06-26
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The prior art is difficult to achieve thinning, low weight per unit area and increase strength of nonwoven fabrics while maintaining the heat resistance and chemical resistance of polyphenylene sulfide fibers.

Method used

By reducing the fiber diameter and controlling the crystallinity within a specific range, ultrafine polyphenylene sulfide fibers with an average fiber diameter of 0.2 μm or more and 5.0 μm or less were prepared, and the crystallinity was calculated by differential scanning calorimetry. It is 0% or more and 15% or less.

Benefits of technology

The excellent adhesion and decentralization of extremely fine polybenzenelin ether fiber is realized, resulting in non -woven fabrics have the characteristics of high strength, thin, and low -unit area weight, and are suitable for a variety of high -performance applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005147428450000031
    Figure BDA0005147428450000031
  • Figure BDA0005147428450000131
    Figure BDA0005147428450000131
  • Figure BDA0005147428450000141
    Figure BDA0005147428450000141
Patent Text Reader

Abstract

The ultrafine polyphenylene sulfide fiber has an average fiber diameter of 0.2 [mu] m or more and 5.0 [mu] m or less and a crystallinity of 0% or more and 15% or less as calculated by differential scanning calorimetry. The present invention relates to an ultrafine polyphenylene sulfide fiber having excellent adhesiveness and dispersibility, a nonwoven fabric formed from the same, and a method for manufacturing the same.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to ultrafine polyphenylene sulfide fibers having excellent adhesiveness and dispersibility, nonwoven fabrics formed therefrom, and methods for producing the same. Background Art

[0002] Polyphenylene sulfide is widely used as a metal substitute and a material that can withstand extreme environments because it has excellent mechanical properties and molding processability in addition to high heat resistance, chemical resistance, electrical insulation, and flame retardancy. The polyphenylene sulfide fiber obtained by fiberizing polyphenylene sulfide effectively utilizes the above characteristics and is used for bag filters, papermaking canvas, electrical insulation paper, battery diaphragms, and various diaphragms. In particular, the characteristics of polyphenylene sulfide such as heat resistance and chemical resistance to high-concentration alkaline solutions, etc., are combined with the ion permeability and gas separation properties of non-woven fabric materials to develop wet non-woven fabrics formed of polyphenylene sulfide fibers for hydrogen manufacturing device diaphragms and fuel cell diaphragms, as well as these diaphragm reinforcement materials.

[0003] In recent years, nonwoven fabrics used for the above-mentioned purposes have been required to be thinner and lighter in weight per unit area in order to make the devices smaller, lighter and more high-performance. In the case of thin nonwoven fabrics with a low weight per unit area, the nonwoven fabrics are prone to breakage due to slight tension changes in the manufacturing process, and there is also a problem that the nonwoven fabrics are prone to tearing due to contact with the edges or burrs of other parts during the template forming process. Therefore, in order to improve the strength, various studies have been conducted to improve the strength and adhesion of the binder fibers, which are components that help to bond the fibers constituting the nonwoven fabrics. It should be noted that in the nonwoven fabric formed of polyphenylene sulfide fibers, the binder fibers also need to be composed of polyphenylene sulfide in order to minimize the damage to the heat resistance and chemical resistance of polyphenylene sulfide.

[0004] Against such a background, in order to obtain polyphenylene sulfide fibers for papermaking having a small heat shrinkage and good water dispersibility, a method for producing polyphenylene sulfide fibers for papermaking has been proposed, which is characterized in that the unstretched polyphenylene sulfide fibers obtained by melt spinning are passed through warm water at 70°C or above for heat treatment, and then passed through a dry heat zone at 70 to 90°C in a relaxed state for a relaxation heat treatment for 5 to 60 minutes (for example, refer to Patent Document 1).

[0005] On the other hand, regarding the high performance of nonwoven fabrics formed from polyphenylene sulfide fibers, the following nonwoven fabrics have been proposed, characterized in that they contain ultrafine acid-resistant fibers A having a fiber diameter of less than 2 μm and acid-resistant fibers B having a fiber diameter larger than that of the aforementioned acid-resistant fibers A (for example, refer to Patent Document 2), and the following nonwoven fabrics have been proposed, characterized in that they contain polyphenylene sulfide fibers having an irregular cross-section and polyphenylene sulfide fibers having a circular cross-section shape having a fiber diameter of less than 5 μm (for example, refer to Patent Document 3).

[0006] In addition, a method for manufacturing filter cloth for bag filters has been proposed, which uses ultrafine fibers with a fiber diameter of 200 to 2000 nm obtained by dissolving and removing the sea component of sea-island type composite fibers composed of sea components and island components (for example, refer to Patent Document 4).

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2010-174400

[0010] Patent Document 2: Japanese Patent Application Publication No. 2020-172729

[0011] Patent Document 3: Japanese Patent Application Publication No. 2020-66818

[0012] Patent Document 4: International Publication No. 2017 / 086186 Summary of the invention

[0013] Problem that the invention aims to solve

[0014] According to the technology of Patent Document 1, polyphenylene sulfide fibers with a small heat shrinkage rate can be obtained by subjecting unstretched polyphenylene sulfide fibers obtained by melt spinning to relaxation heat treatment in the production process to shrink them. However, since the unstretched polyphenylene sulfide fibers obtained by this method have a substantially large fiber diameter, it is difficult to obtain a thin nonwoven fabric with a low basis weight.

[0015] In addition, the techniques of Patent Documents 2 and 4 relate to nonwoven fabrics obtained by using ultrafine polyphenylene sulfide fibers having a fiber diameter of 2 μm or less. According to this technique, it is possible to achieve high performance of nonwoven fabrics, but since the binder fibers exemplified are ordinary undrawn polyphenylene sulfide yarns, it is difficult to obtain thin nonwoven fabrics with low weight per unit area. Furthermore, although a method for producing ultrafine polyphenylene sulfide fibers by removing the sea component of sea-island fibers obtained by using polyphenylene sulfide fibers from the island component is exemplified, the ultrafine polyphenylene sulfide fibers obtained by this production method are crystallized by heating during sea removal, and therefore the adhesiveness when used as binder fibers is insufficient.

[0016] Furthermore, the technology of Patent Document 3 can obtain a nonwoven fabric that is less likely to break when produced by a wet papermaking method by using polyphenylene sulfide fibers having a special cross section and a polyphenylene sulfide fiber having a circular cross section with a fiber diameter of 5 μm or less. However, the effect of improving the strength of the nonwoven fabric obtained by this method is limited, and it is difficult to achieve a strength that can provide practical use when it is desired to obtain a thin nonwoven fabric with a low unit weight as required in recent years.

[0017] Therefore, the present invention has been made in view of the above circumstances, and an object of the present invention is to provide ultrafine polyphenylene sulfide fibers having excellent adhesiveness and water dispersibility, a nonwoven fabric formed therefrom, and a method for producing the same.

[0018] Means for solving problems

[0019] The inventors of the present invention have conducted research and found that it is effective to reduce the fiber diameter of the binder fiber that helps to bond the fibers together in the fibers constituting the nonwoven fabric in order to reduce the thickness, reduce the weight per unit area, and improve the strength of the nonwoven fabric formed of polyphenylene sulfide fibers. On the other hand, when it is desired to reduce the fiber diameter, although a method of drawing an undrawn yarn or a method of removing the sea component of the sea-island fiber by dissolving it with a high-temperature solution can be used, the binder fiber obtained is a fiber with low adhesion due to crystallization caused by molecular orientation and heat.

[0020] Therefore, the present inventors have made further intensive studies to achieve the above-mentioned problems, and as a result, have found that even when the fiber diameter is reduced, by setting the crystallinity calculated by differential scanning calorimetry to a specific range, ultrafine polyphenylene sulfide fibers having excellent adhesiveness and dispersibility can be obtained, thereby completing the present invention.

[0021] The present invention solves the above-mentioned problems. The ultrafine polyphenylene sulfide fiber of the present invention has an average fiber diameter of 0.2 μm or more and 5.0 μm or less and a crystallinity calculated by differential scanning calorimetry of 0% or more and 15% or less.

[0022] According to a preferred embodiment of the ultrafine polyphenylene sulfide fiber of the present invention, the ultrafine polyphenylene sulfide fiber is a fiber with a profiled cross section, and a profile degree defined by the following formula is 1.2 or more.

[0023] Degree of irregularity = minimum circumscribed circle diameter / maximum inscribed circle diameter

[0024] Here, the minimum circumscribed circle diameter is the diameter (μm) of the smallest circle that includes the entire fiber cross section, and the maximum inscribed circle diameter is the diameter (μm) of the largest circle that falls within the fiber cross section.

[0025] According to a preferred embodiment of the ultrafine polyphenylene sulfide fiber of the present invention, the average fiber length is 0.1 mm to 6.0 mm.

[0026] The method for producing ultrafine polyphenylene sulfide fibers of the present invention is a method for producing ultrafine polyphenylene sulfide fibers, comprising removing the sea component from an undrawn fiber having a sea-island type composite cross section in which polyphenylene sulfide is blended in an alkaline aqueous solution at a temperature of 70° C. or lower, thereby obtaining a fiber having an average fiber diameter of 0.2 μm or more and 5.0 μm or less and a crystallinity of 0% or more and 15% or less as calculated by differential scanning calorimetry.

[0027] The method for producing a nonwoven fabric of the present invention comprises mixing the ultrafine polyphenylene sulfide fibers and the drawn polyphenylene sulfide fibers in a papermaking dispersion to make paper, and then subjecting the mixture to thermocompression bonding at a temperature of 130° C. to 250° C.

[0028] Effects of the Invention

[0029] According to the present invention, ultrafine polyphenylene sulfide fibers having excellent adhesiveness and dispersibility can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a conceptual diagram for explaining an example of the fiber cross section of the ultrafine polyphenylene sulfide fiber of the present invention and a method for measuring the degree of irregularity. DETAILED DESCRIPTION

[0031] The ultrafine polyphenylene sulfide fiber of the present invention has an average fiber diameter of 0.2 μm or more and 5.0 μm or less, and a crystallinity calculated by differential scanning calorimetry of 0% or more and 15% or less. The constituent elements are described in detail below, but the present invention is not limited to the scope of the following description unless it exceeds the gist of the present invention.

[0032] [Ultra-fine polyphenylene sulfide fiber]

[0033] The polyphenylene sulfide according to the present invention is a polymer composed of a p-phenylene sulfide unit represented by the structural formula (1) or a diphenylene sulfide unit such as a m-phenylene sulfide unit as a main repeating unit.

[0034]

[0035] The polyphenylene sulfide of the present invention preferably contains 60 mol% or more of p-phenylene sulfide units. When the p-phenylene sulfide units are preferably 60 mol% or more, more preferably 70 mol% or more, and even more preferably 80 mol% or more, a fiber having excellent heat resistance is obtained. In addition, when processed into a nonwoven fabric, a nonwoven fabric having excellent strength is obtained.

[0036] The polyphenylene sulfide of the present invention may contain copolymer units other than the diphenylene sulfide units as long as the effects of the present invention are not impaired. Examples of copolymer units other than the diphenylene sulfide units include aromatic sulfides such as triphenylene sulfide and bisphenylene sulfide, or alkyl-substituted or halogen-substituted products thereof.

[0037] The polyphenylene sulfide of the present invention may contain various additives such as inorganic substances such as titanium oxide, silicon dioxide, barium oxide, calcium carbonate, carbon black, colorants such as dyes or pigments, flame retardants, fluorescent whitening agents, antioxidants, or ultraviolet absorbers, within the range not impairing the effects of the present invention.

[0038] The ultrafine polyphenylene sulfide fiber of the present invention may be a single component fiber or a composite fiber obtained by compounding two or more resins. When the ultrafine polyphenylene sulfide fiber is a composite fiber, its composite form is not particularly limited as long as it does not impair the effect of the present invention, and it can be appropriately selected from core-sheath type, island-in-the-sea type, shoulder-to-shoulder type, eccentric core-sheath type, mixed type, etc. It should be noted that when the ultrafine polyphenylene sulfide fiber is used as a composite fiber, the resin used together with the polyphenylene sulfide is preferably a polyphenylene sulfide with a different copolymerization ratio of meta-phenylene sulfide units from the viewpoint of process stability and flexibility in the manufacturing process. For example, in the case of a core-sheath type composite fiber, the core component may be a polyphenylene sulfide formed only by p-phenylene sulfide units, and the sheath component may be a polyphenylene sulfide obtained by copolymerizing meta-phenylene sulfide units, or in the case of an island-in-the-sea type composite fiber, the sea component may be a polyphenylene sulfide formed only by p-phenylene sulfide units, and the island component may be a polyphenylene sulfide obtained by copolymerizing meta-phenylene sulfide units, etc.

[0039] The cross-sectional shape of the ultrafine polyphenylene sulfide fiber of the present invention is not limited in any way and may be a circular cross-section, or may be a multi-lobed cross-section such as a Y-shaped cross-section or a triangular cross-section, a flat cross-section, an S-shaped cross-section, a cross cross-section, a hollow cross-section, or any other irregular cross-sectional shape.

[0040] The ultrafine polyphenylene sulfide fiber of the present invention preferably has a non-shapedness defined by the following formula of 1.2 or more. By setting the non-shapedness preferably to 1.2 or more, more preferably to 1.5 or more, and still more preferably to 1.7 or more, the specific surface area of ​​the fiber becomes larger, so that the bonding area when used as an adhesive increases, and a nonwoven fabric having excellent strength is obtained. In addition, there is no particular limitation on the upper limit of the non-shapedness, and the upper limit that can be achieved in the present invention is about 500.

[0041] The degree of irregularity mentioned here is measured according to the following method, using Figure 1 Provide detailed explanation.

[0042] Figure 1 An example of the fiber cross section of the ultrafine polyphenylene sulfide fiber of the present invention is shown.

[0043] First, the cross section of the fiber is imaged with a scanning electron microscope at a magnification that allows one fiber to be observed. Using the image after the image is taken, the minimum circumscribed circle and the maximum inscribed circle in the cross section are constructed using image analysis software, and the degree of irregularity is calculated using the following formula. The above degree of irregularity is measured for 20 randomly selected fibers, and a simple numerical average is calculated, and the second decimal place is rounded off.

[0044] Degree of irregularity = minimum circumscribed circle diameter / maximum inscribed circle diameter

[0045] Here, the minimum circumscribed circle diameter is the diameter (μm) of the smallest circle that includes the entire fiber cross section, and the maximum inscribed circle diameter is the diameter (μm) of the largest circle that falls within the fiber cross section.

[0046] The average fiber diameter of the ultrafine polyphenylene sulfide fiber of the present invention is 0.2 μm or more and 5.0 μm or less. By setting the average fiber diameter to 0.2 μm or more, preferably 0.4 μm or more, and more preferably 0.5 μm or more, the fibers are less likely to be entangled with each other, and the dispersion of the fibers is improved, so that the uniformity of the weight per unit area when made into a nonwoven fabric is improved. In addition, by setting the average fiber diameter to 5.0 μm or less, preferably 3.0 μm or less, and more preferably 2.0 μm or less, the number of constituent fibers with the same fineness and the same weight per unit area increases, so that the number of bonding points when used as an adhesive increases, and a nonwoven fabric with excellent strength is obtained.

[0047] The average fiber diameter (μm) of the fibers mentioned here is determined as follows.

[0048] (1) An image of a cross section of a fiber is captured using a scanning electron microscope at a magnification sufficient to observe a single fiber.

[0049] (2) Using the captured image, the area Af (μm) formed by the cross-sectional profile of the single fiber is measured using image analysis software. 2 ), calculate the diameter of a perfect circle having the same area as the area Af.

[0050] (3) The above diameters were measured for 100 randomly selected fibers, and the simple numerical average was obtained to calculate the average fiber diameter (μm), with the second decimal place rounded off.

[0051] Although the ultrafine polyphenylene sulfide fibers of the present invention can be used as long fibers, they can also be cut into short fibers by cutting them into a certain length before processing into nonwoven fabrics or the like.

[0052] When the ultrafine polyphenylene sulfide fiber of the present invention is made into short fibers, the average fiber length is preferably 0.1 mm or more and 6.0 mm or less. By preferably setting the average fiber length to 0.1 mm or more, more preferably 0.2 mm or more, and further preferably 0.3 mm or more, the fibers are less likely to fall off during the processing step of the nonwoven fabric. In addition, by preferably setting the average fiber length to 6.0 mm or less, more preferably 4.0 mm or less, and further preferably 2.0 mm or less, the fibers are less likely to be entangled with each other, thereby improving the dispersion of the fibers, and thus improving the quality when made into a nonwoven fabric.

[0053] The average fiber length mentioned here is obtained based on "8.4.1. Average fiber length (c direct method)" of JIS L1015:2010 "Test method for length of chemical staple fibers".

[0054] The ultrafine polyphenylene sulfide fiber of the present invention has a crystallinity of 0% or more and 15% or less as calculated by differential scanning calorimetry. By setting the crystallinity to 0% or more, preferably 1% or more, the fiber has excellent handling properties in high-order processes. In addition, by setting the crystallinity to 15% or less, preferably 12% or less, more preferably 10% or less, and further preferably 9% or less, the fiber has excellent adhesiveness and is suitable for a binder fiber.

[0055] The crystallinity (%) of the fiber mentioned here is obtained in the following manner.

[0056] (1) About 5 mg of the fiber was weighed using an electronic balance, and then placed in a differential scanning calorimeter. Differential scanning calorimetry was performed under nitrogen at a heating rate of 16°C / min and a measurement temperature range of 50 to 320°C.

[0057] (2) The crystallization heat ΔHc (J / g) is calculated from the area of ​​the exothermic peak in the obtained measurement result (DSC curve), and the crystal melting heat ΔHm (J / g) is calculated from the area of ​​the endothermic peak. In addition, when multiple exothermic peaks and endothermic peaks are observed, ΔHc and ΔHm are calculated by adding up the values ​​obtained by the areas of all the peaks.

[0058] (3) The measurement position was changed based on one level and three measurements were performed to obtain a simple numerical average. After calculating ΔHc and ΔHm, the crystallinity (%) was calculated using the following formula (1), and the first decimal place was rounded off.

[0059] Crystallinity (%) = (ΔHm-ΔHc) / ΔHm 0 ×100…(1)

[0060] Here, ΔHm 0 It is the heat of complete crystallization fusion (J / g). In the case of polyphenylene sulfide, 140.1 J / g is generally used.

[0061] [Non-woven fabric]

[0062] The nonwoven fabric of the present invention is a nonwoven fabric containing the ultrafine polyphenylene sulfide fibers. By containing the ultrafine polyphenylene sulfide fibers, the number of fibers constituting the nonwoven fabric increases, so that the nonwoven fabric is not easily broken and has excellent strength. In addition, since the constituent fibers themselves are thin, a thin nonwoven fabric can be obtained.

[0063] The ratio of the ultrafine polyphenylene sulfide fibers in the nonwoven fabric of the present invention is preferably 10% by mass or more and 80% by mass or less. By setting the ratio of the ultrafine polyphenylene sulfide fibers to preferably 10% by mass or more, more preferably 20% by mass or more, and further preferably 30% by mass or more, the number of fibers constituting the nonwoven fabric increases, and the number of bonding points between the fibers increases, thereby providing a nonwoven fabric having excellent mechanical properties. In addition, by setting the ratio of the ultrafine polyphenylene sulfide fibers to preferably 80% by mass or less, more preferably 75% by mass or less, and further preferably 70% by mass or less, a nonwoven fabric having moderate air permeability and softness is provided.

[0064] The fibers other than the ultrafine polyphenylene sulfide contained in the nonwoven fabric of the present invention are not particularly limited, and examples thereof include fibers made of polyphenylene sulfide, polypropylene, polyethylene, poly-4-methyl-1-pentene, polycarbonate, polyacrylate, polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate, polylactic acid, aromatic polyester, polyamide, aromatic polyamide, thermoplastic polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, and copolymers thereof. Among them, fibers made of polyphenylene sulfide are preferably used from the viewpoints of chemical resistance, heat resistance, and adhesion to ultrafine polyphenylene sulfide fibers.

[0065] The nonwoven fabric of the present invention preferably has a weight per unit area of ​​2 g / m 2 Above and 80g / m 2 The weight per unit area is preferably 2 g / m 2 More preferably 5g / m 2 The above nonwoven fabric has excellent strength. In addition, the weight per unit area is preferably 80 g / m 2 Below, more preferably 50g / m 2 Next, a nonwoven fabric having excellent softness is obtained.

[0066] The nonwoven fabric weight per unit area (g / m 2 ) is a value measured and calculated by the following procedure based on "6.2 Mass per unit area (ISO method)" of JIS L1913:2010 "General nonwoven fabric test methods".

[0067] (1) A 20 cm x 25 cm test piece was selected from the nonwoven fabric.

[0068] (2) For the selected test piece, measure the mass (g) under standard conditions and convert it into 2 Mass of area (g / m 2 ).

[0069] (3) Based on one level, the selected position of the test piece was changed and the measurement was performed three times. The arithmetic mean was rounded to the first decimal place and the value obtained was calculated as the unit area weight (g / m 2 ).

[0070] The thickness of the nonwoven fabric of the present invention is preferably 170 μm or less. By setting the thickness of the nonwoven fabric to preferably 170 μm or less, and more preferably 155 μm or less, a nonwoven fabric having moderate air permeability and softness is obtained. In addition, there is no particular lower limit for the thickness of the nonwoven fabric of the present invention, but in order to obtain a nonwoven fabric having practical strength, it is preferably 2 μm or more, and more preferably 5 μm or more.

[0071] The thickness (μm) of the nonwoven fabric mentioned here is based on JIS P8118: 2014 "Paper and paperboard-Test method for thickness, density and specific volume". 20 10 cm × 10 cm test pieces are selected, and a thickness meter (for example, "Micrometer" manufactured by Mitsuyo Co., Ltd.) is used for each piece to measure the thickness of the 20 test pieces, and the simple numerical average is obtained to calculate the thickness (μm) of the nonwoven fabric, and the first decimal place is rounded off to obtain the value.

[0072] The strength of the nonwoven fabric of the present invention is preferably 10N / 15mm or more. By setting the strength of the nonwoven fabric to preferably 10N / 15mm or more, more preferably 15N / 15mm or more, and further preferably 20N / 15mm or more, a nonwoven fabric suitable for diaphragm use and filter use that is not easily broken is obtained. In addition, the upper limit of the strength of the nonwoven fabric of the present invention is not particularly limited, and the nonwoven fabric of the present invention can achieve a strength of about 100N / 15mm.

[0073] The strength of the nonwoven fabric (N / 15mm) mentioned here is the value of the maximum point load measured under the conditions of a sample width of 15mm, an initial length of 20mm and a tensile speed of 20mm / min using a tensile testing machine (e.g., UTM-III-100 manufactured by Orientec Corporation) for a nonwoven fabric cut out with a sample width of 15mm. The simple numerical average of the five measured values ​​is calculated to calculate the strength of the nonwoven fabric (N / 15mm), and the value is rounded off to the first decimal place.

[0074] The strength per unit area weight of the nonwoven fabric of the present invention is preferably 0.25 (N / 15 mm) / (g / m 2 ) or more. The strength of the nonwoven fabric is preferably set to 0.25 (N / 15mm) / (g / m 2 ) or more, more preferably 0.38 (N / 15mm) / (g / m 2 ) or more, and more preferably 0.50 (N / 15mm) / (g / m 2 ) or more, thereby becoming a nonwoven fabric suitable for membrane and filter applications and not easily broken. In addition, there is no particular upper limit on the strength of the nonwoven fabric of the present invention. The strength that the nonwoven fabric of the present invention can achieve is 2.50 (N / 15mm) / (g / m 2 )about.

[0075] The strength per unit area weight of the nonwoven fabric mentioned here is ((N / 15mm) / (g / m 2 )) is a value obtained by dividing the strength of the nonwoven fabric obtained above by the weight per unit area, and further rounding off the third decimal place of the value.

[0076] The ultrafine polyphenylene sulfide fiber of the present invention and the nonwoven fabric formed therefrom have excellent long-term heat resistance and chemical resistance, mechanical properties, electrical insulation, and flame retardancy. These characteristics can be effectively utilized and the nonwoven fabric is suitable for use in diaphragms such as hydrogen production device diaphragms, fuel cell diaphragms, battery diaphragms, electrode diaphragms, and diaphragm reinforcement materials thereof, filter applications such as bag filters, liquid medicine filters, food filters, chemical filters, oil filters, engine oil filters, air cleaning filters, and paper applications such as electrical insulating paper. It can be used in various uses such as heat-resistant work clothes for roads, fire fighting clothes, safety clothes, test work clothes, thermal insulation clothes, flame-retardant clothes, papermaking felt, heat-resistant felt, mold release material, papermaking dryer canvas, heart patch, artificial skin, printed circuit board substrate, swing printing dust collector (コピーローリングクリーナー), ion exchange substrate, oil retention material, insulation material, cushion material, mesh conveyor, etc., especially as a diaphragm use and paper use required for thinning and low unit area weight, and these uses are not limited.

[0077] [Ultrafine polyphenylene sulfide fiber and method for producing nonwoven fabric]

[0078] A preferred embodiment for producing the ultrafine polyphenylene sulfide fibers and nonwoven fabric of the present invention will be described in detail below.

[0079] The method for producing ultrafine polyphenylene sulfide fibers of the present invention is a method for producing ultrafine polyphenylene sulfide fibers, comprising removing the sea component from an undrawn fiber having an island-in-sea type composite cross section in which polyphenylene sulfide is arranged as an island component in an alkaline aqueous solution at a temperature of 70° C. or lower to obtain a fiber having an average fiber diameter of 0.2 μm or more and 5.0 μm or less and a crystallinity of 0% or more and 15% or less as calculated by differential scanning calorimetry.

[0080] The polyphenylene sulfide used is preferably dried before melt spinning to prevent water from entering and remove oligomers, and to improve spinning properties. Drying conditions are usually 100 to 200° C. and vacuum drying for 1 to 24 hours.

[0081] In melt spinning, a melt spinning method using an extruder such as a pressure melting type, a single screw or a twin screw extruder can be applied. The extruded polyphenylene sulfide is metered through a metering device such as a gear pump via a pipe, and after passing through a filter for removing foreign matter, it is guided to a spinning die. At this time, the temperature from the polymer pipe to the spinning die (spinning temperature) is preferably 290°C or more in order to improve fluidity, and is preferably 380°C or less in order to suppress thermal decomposition of the polymer.

[0082] The ultrafine polyphenylene sulfide fiber of the present invention can be obtained by removing the polymer of the sea component of the island-in-sea composite fiber having an island-in-sea composite cross section in which polyphenylene sulfide is arranged in the island component. It should be noted that the cross-sectional shape of the ultrafine polyphenylene sulfide fiber of the present invention is almost the same as the cross-sectional shape of the island component of the above-mentioned island-in-sea composite fiber, so by making the cross-sectional shape of the island component into an arbitrary shape, an ultrafine polyphenylene sulfide fiber having a desired cross-sectional shape can be obtained. The method of controlling the cross-sectional shape of the island component is not particularly limited, and for example, the methods disclosed in Japanese Patent Application Laid-Open No. 2010-216042 and Japanese Patent Application Laid-Open No. 2016-188454 can be cited as preferred methods.

[0083] The sea component of the above-mentioned island-in-sea composite fiber is suitable for using a readily soluble polymer. The readily soluble polymer mentioned here, for example, can be selected from melt-molded polymers such as polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polypropylene terephthalate, polypropylene, polyolefin, polycarbonate, polyacrylate, polyamide, polylactic acid, thermoplastic polyurethane, etc., and copolymers thereof. Among them, from the perspective of simplifying the dissolution process of the sea component, the sea component is preferably a copolyester, polylactic acid, polyvinyl alcohol, etc. that show easy dissolution in an aqueous solvent or hot water, preferably a polyester formed by copolymerizing 5-sodium sulfonate of isophthalic acid alone, or a polyester obtained by copolymerizing polyethylene glycol in order to further improve dissolution. On the other hand, when the pyrolysis of the readily soluble polymer progresses during spinning, the cross-sectional formability and spinnability of the composite fiber deteriorate, so it is necessary to be difficult to pyrolyze at the above-mentioned spinning temperature, that is, high heat resistance. From such a viewpoint, a polyester obtained by copolymerizing 5-sodium sulfoisophthalate alone is more preferred.

[0084] When a polyester obtained by copolymerizing 5-sodium sulfoisophthalic acid alone is used as the sea component, the copolymerization amount of 5-sodium sulfoisophthalic acid is preferably 2 mol% or more and 20 mol% or less from the viewpoint of both solubility in aqueous solvents and heat resistance. By setting the copolymerization amount of 5-sodium sulfoisophthalic acid to preferably 2 mol% or more, more preferably 3 mol% or more, the solubility in aqueous solvents is improved, so that the sea component can be easily removed when used as the sea component of the sea-island type composite fiber. In addition, setting the copolymerization amount of 5-sodium sulfoisophthalic acid to preferably 20 mol% or less, more preferably 15 mol% or less, can provide a polymer having excellent heat resistance.

[0085] The island-in-sea composite fiber used in the present invention is prepared by melting polyphenylene sulfide and other component polymers, metering them through a polymer pipe by a known metering device such as a gear pump, passing through a filter for removing foreign matter, and then guiding them to each spinning die. The polymers guided to the spinning die are shaped into an arbitrary composite form in the spinning die, merge, and are discharged from the die hole as the island-in-sea composite fiber.

[0086] The spinning die used for discharge preferably has a die hole diameter D of not less than 0.1 mm and not more than 0.6 mm. In addition, L / D, defined as the quotient obtained by dividing the die hole forming section length (range length) L (the length of the straight tube portion with the same diameter as the die hole) by the hole diameter, is not less than 1 and not more than 10.

[0087] The shape and cross-sectional area of ​​the island component in the sea-island composite fiber can be the same as the area of ​​the fiber cross section calculated from the above-mentioned fiber shape and average fiber diameter. For example, by making the polyphenylene sulfide as the island component into a circle with a diameter of 2.0 μm, a circular cross-sectional fiber with an average fiber diameter of 2.0 μm can be produced. Therefore, in order to obtain an ultrafine polyphenylene sulfide fiber with an average fiber diameter of 0.2 μm or more and 5.0 μm or less, the diameter of the island component can be set to 0.2 μm or more and 5.0 μm or less.

[0088] The number of island components in the sea-island type composite fiber is not particularly limited, but is preferably 20 or more and 4000 or less. By setting the number of island components preferably to 20 or more, more preferably to 100 or more, and further preferably to 200, the diameter of the island components can be reduced, and thus the average fiber diameter of the ultrafine polyphenylene sulfide fiber can be reduced. In addition, by setting the number of island components preferably to 4000 or less, and more preferably to 3000 or less, the fiber cross-section formability becomes good, so that a fiber with a small deviation in fiber diameter can be obtained.

[0089] The island-in-the-sea composite fiber discharged from the die hole is cooled and solidified by blowing cooling wind (air). From the perspective of cooling efficiency, the temperature of the cooling wind can be determined by balancing the cooling wind speed, and a preferred solution is 30°C or less. By preferably setting the temperature of the cooling wind to 30°C or less, the solidification behavior caused by cooling is stable and the fiber diameter uniformity is high.

[0090] In addition, the cooling air preferably flows toward the undrawn fibers discharged from the die in a direction substantially perpendicular to the fiber axis. At this time, the speed of the cooling air is preferably 10 m / min or more from the viewpoint of cooling efficiency and uniformity of fineness, and preferably 100 m / min or less from the viewpoint of yarn making stability.

[0091] The undrawn fiber that has been cooled and solidified is drawn through a roller (godnet roller) rotating at a constant speed. The drawing speed is preferably 300 m / min or more to improve linear uniformity and productivity, and preferably 1500 m / min or less to prevent molecular chain orientation.

[0092] The undrawn fiber obtained in this manner is not drawn but is directly supplied to the next step in the state of the undrawn fiber.

[0093] The obtained undrawn fiber can be subjected to crimping by a crimping machine and shape fixing by a setting machine at a temperature of 70° C. or lower as needed. The fibers are entangled with each other by crimping, thereby increasing the bonding area between the fibers and obtaining a nonwoven fabric with excellent mechanical strength.

[0094] The number of crimps in the crimp is preferably 2 peaks (2 peaks) / 25 mm or more and 15 peaks / 25 mm or less. By setting the number of crimps to preferably 2 peaks / 25 mm or more, the fibers are easily entangled with each other, and a nonwoven fabric having excellent mechanical strength is obtained. In addition, by preferably setting the number of crimps to preferably 15 peaks / 25 mm or less, the dispersibility of the fibers in the dispersion is improved, and a homogeneous nonwoven fabric is obtained.

[0095] Then, the obtained island-in-the-sea composite fiber can be cut into a predetermined length with a shearing machine to obtain short fibers. The fiber length of the short fibers is preferably 0.1 mm or more and 6.0 mm or less. By preferably setting the average fiber length to 0.1 mm or more, more preferably 0.2 mm or more, and further preferably 0.3 mm or more, the fibers become difficult to fall off during the processing of the nonwoven fabric. In addition, by preferably setting the average fiber length to 6.0 mm or less, more preferably 4.0 mm or less, and further preferably 2.0 mm or less, the fibers are not easily entangled with each other and the dispersion of the fibers is improved, so the uniformity of the weight per unit area when the nonwoven fabric is made is improved.

[0096] In addition, the short fiberization by a shearing machine can be carried out after obtaining the ultrafine polyphenylene sulfide fibers by the method described later.

[0097] In order to obtain the ultrafine polyphenylene sulfide fiber of the present invention, it is sufficient to immerse the above-mentioned sea-island type composite fiber in a solvent that can dissolve the sea component, and remove the polymer of the sea component. In the case of the polymer of the sea component being a copolymerized polyethylene terephthalate formed by copolymerizing 5-sodium sulfonate of isophthalic acid, an alkaline aqueous solution such as an aqueous solution of sodium hydroxide can be used as a solvent. At this time, the bath ratio of the sea-island type composite fiber to the alkaline aqueous solution (mass of the sea-island type composite fiber (g) / mass of the alkaline aqueous solution (g)) is preferably 1 / 10000 or more and 1 / 5 or less, and more preferably 1 / 5000 or more and 1 / 10 or less. By being within this range, it is possible to suppress unnecessary entanglement of the ultrafine fibers with each other when the sea component is dissolved.

[0098] At this time, the alkali concentration of the alkaline aqueous solution is preferably 0.1 mass % to 5.0 mass %, more preferably 0.5 mass % to 3 mass %. By setting it within the above range, the dissolution of the sea component can be completed in a short time.

[0099] It is important to set the temperature of the alkaline aqueous solution to 70° C. or less when removing the sea component. By setting the temperature of the alkaline aqueous solution to 70° C. or less, preferably 65° C. or less, and more preferably 60° C. or less, crystallization does not occur during the elution treatment, so that ultrafine polyphenylene sulfide fibers with low crystallinity and excellent adhesiveness can be obtained.

[0100] The treatment time in the alkaline aqueous solution is preferably 10 minutes or more and 100 minutes or less. By setting the treatment time preferably to 10 minutes or more, more preferably to 20 minutes or more, it is difficult for the sea component to remain dissolved, and the ultrafine polyphenylene sulfide fiber with excellent dispersibility is obtained. In addition, by setting the treatment time preferably to 100 minutes or less, more preferably to 70 minutes or less, it is difficult for crystallization to occur during the treatment, and the ultrafine polyphenylene sulfide fiber with excellent adhesiveness is obtained.

[0101] Furthermore, it is preferred to add a surfactant to the above-mentioned alkaline aqueous solution as a dissolution promoter of the sea component. As the surfactant, cationic surfactants, anionic surfactants, nonionic surfactants, etc. can be listed. When polyester is used as the easily soluble polymer, a cationic surfactant is preferably used. In addition, the concentration of the surfactant in the alkaline aqueous solution is preferably 0.05 mass% or more and 2 mass% or less, and more preferably 0.1 mass% or more and 1 mass% or less relative to the weight of the alkaline aqueous solution. By being within the above range, the dissolution of the sea component can be completed in a short time even at a temperature below 70°C.

[0102] By using short fibers formed of the ultrafine polyphenylene sulfide fibers obtained as described above as binder fibers and dispersing them in water together with the binder fibers, the papermaking liquid can be prepared. In addition, generally, polyphenylene sulfide drawn fibers can be used as the binder fibers.

[0103] The ratio of the binder fiber to the binder fiber in the papermaking liquid is preferably 10% by mass or more and 80% by mass or less. By setting the ratio of the binder fiber to the binder fiber preferably to 10% by mass or more, more preferably to 20% by mass or more, and further preferably to 30% by mass or more, the number of bonding points between the fibers increases, and a nonwoven fabric having excellent mechanical properties is obtained. In addition, by setting the ratio of the binder fiber to the binder fiber preferably to 80% by mass or less, more preferably to 75% by mass or less, and further preferably to 70% by mass or less, a nonwoven fabric having moderate air permeability and softness is obtained.

[0104] The papermaking liquid is supplied to a papermaking machine to obtain a nonwoven fabric. The basis weight of the obtained nonwoven fabric can be changed by adjusting the fiber concentration of the papermaking liquid supplied.

[0105] The nonwoven fabric obtained as described above is preferably dried to remove moisture. The drying temperature is preferably 70° C. or lower to avoid a decrease in hot tack due to crystallization of the amorphous portion.

[0106] The nonwoven fabric obtained in this way is heat-bonded by a flat heating calender or a calender roller, so that the ultrafine polyphenylene sulfide fibers of the present invention generate heat bonding between the binder fibers to form a nonwoven fabric with excellent mechanical properties. The heat bonding temperature is preferably 130°C or more and 250°C or less, and the bonding time is preferably set to 10 minutes or less. By setting the heat bonding temperature preferably to 130°C or more, more preferably to 150°C or more, and further preferably to 170°C or more, the ultrafine polyphenylene sulfide fibers of the present invention are heat bonded to form a nonwoven fabric with excellent mechanical properties. In addition, by setting the heat bonding temperature preferably to 250°C or less, the occurrence of wrinkles caused by the heat shrinkage of the nonwoven fabric during heat bonding can be suppressed. Furthermore, by setting the bonding time preferably to 10 minutes or less, more preferably to 5 minutes or less, the softness of the nonwoven fabric can be suppressed from being reduced due to excessive crystallization.

[0107] Example

[0108] The present invention will be described in detail below based on examples. However, the present invention is not limited to these examples. It should be noted that in the measurement of various physical properties, matters not particularly described were measured based on the above-mentioned methods.

[0109] (1) Average fiber diameter

[0110] The measurement was performed as described above using a scanning electron microscope “S-5500” manufactured by Hitachi High-Tech Novel Devices, Ltd. and image analysis using “WinROOF2015” manufactured by Mitani Shoji Co., Ltd.

[0111] (2) Degree of heterogeneity

[0112] The measurement was performed as described above using a scanning electron microscope “S-5500” manufactured by Hitachi High-Tech Novel Devices Co., Ltd. and image analysis software “WinROOF2015” manufactured by Mitani Shoji Co., Ltd.

[0113] (3) Average fiber length

[0114] The measurement was performed as described above based on "8.4.1. Average fiber length (c direct method)" of JIS L1015:2010 "Testing methods for chemical staple fibers".

[0115] (4) Crystallinity

[0116] The measurement was performed as described above using a differential scanning calorimeter "DSC Q2000" manufactured by TA Instruments.

[0117] (5) Weight per unit area

[0118] The measurement was performed as described above based on "6.2 Mass per unit area" of JIS L1913:2010 "General nonwoven fabric test methods".

[0119] (6) Thickness of nonwoven fabric

[0120] The measurement was performed as described above using “Micrometer” manufactured by Mitsutoyo Co., Ltd. based on JIS P8118:2014 “Paper and paperboard—Test methods for thickness, density and specific volume”.

[0121] (7) Strength of nonwoven fabric

[0122] The nonwoven fabrics produced in the respective embodiments and comparative examples were measured as described above using a tensile testing machine Tensilon (UTM-III-100 manufactured by Orientec Corporation).

[0123] (8) Quality of nonwoven fabrics

[0124] The quality of the obtained nonwoven fabric was evaluated based on the following three grades.

[0125] A: No uneven weight per unit area and good uniformity of appearance

[0126] B: Fiber bundles and fiber aggregates can be identified in non-woven fabrics

[0127] C: Cracks or pinholes occurred in the nonwoven fabric.

[0128] [Reference Example 1]

[0129] After vacuum drying at 150°C for 12 hours, polyphenylene sulfide consisting only of p-phenylene sulfide units was melt-spun at a spinning temperature of 330°C. In melt spinning, polyphenylene sulfide was melt-extruded using a twin-screw extruder, metered using a gear pump, and supplied to the spinning assembly after passing through a filter for removing foreign matter. Then, a die with 36 holes having discharge holes was used to discharge polyphenylene sulfide at a single hole discharge rate of 0.2 g / min. The introduction hole located directly above the die hole was a straight hole, and a conical spinneret was used for the connection between the introduction hole and the die hole. After the polyphenylene sulfide discharged from the die passed through a 50 mm heat preservation area, it was air-cooled in a range of 1.0 m using a unidirectional flow type cooling device at a temperature of 25°C and a wind speed of 18 m / min. Then, an oil agent was applied, and 36 filaments were collectively passed through a first godet roller and a second godet roller at a speed of 1000 m / min, and the 36 filaments were wound up by a winder to obtain undrawn fibers.

[0130] Next, the obtained undrawn fiber was drawn to 3.0 times between rolls heated to 90° C., and then heat-set using rolls heated to 200° C. to obtain drawn polyphenylene sulfide fiber.

[0131] Then, the obtained drawn polyphenylene sulfide fibers were cut with a shearing machine to obtain short fibers having an average fiber length of 6 mm.

[0132] [Example 1]

[0133] Polyphenylene sulfide consisting of only p-phenylene sulfide units was used as the island component, and polyethylene terephthalate obtained by copolymerization with 5.0 mol% of sodium 5-sulfonate of isophthalic acid was used as the sea component. After vacuum drying each polymer at 150°C for 12 hours, melt spinning was performed at a spinning temperature of 310°C. In melt spinning, the island component and the sea component were melted separately, metered by a gear pump through a polymer pipe, passed through a filter for removing foreign matter, and then supplied to a spinning pack. Then, a sea-island composite die (number of islands: 1000, D: 0.4 mm, L: 0.8 mm) in which the shape of the island component was circular was used, and the melted and discharged filaments were cooled and solidified at a composite ratio of 40 / 60 of the sea / island component, and an oil agent was applied, and an undrawn fiber having a sea-island composite cross section was obtained by winding at a spinning speed of 1000 m / min (single hole discharge amount: 2.6 g / min).

[0134] Next, the obtained island-in-sea composite fibers were cut with a shearing machine to obtain short fibers with an average fiber length of 0.5 mm. Then, the obtained short fibers were dissolved in a 3% by mass sodium hydroxide aqueous solution (bath ratio 1 / 100) heated to 50° C. for 40 minutes to obtain a binder fiber formed of ultrafine polyphenylene sulfide fibers. It should be noted that "DY-1125K (quaternary ammonium salt type cationic surfactant)" manufactured by Lifen Specialty Chemicals Co., Ltd. was added to the sodium hydroxide aqueous solution at a mass % of 0.5% relative to the mass of the sodium hydroxide aqueous solution as a dissolution accelerator for treatment.

[0135] The ultrafine polyphenylene sulfide fibers as the binder fibers were mixed in a ratio of 50% by mass and the drawn polyphenylene sulfide fibers obtained in Reference Example 1 as the binder fibers were mixed in a ratio of 50% by mass into a papermaking dispersion to adjust the fiber concentration to 0.4% by mass. The papermaking liquid was supplied to a simple papermaking machine to obtain a paper having a unit weight of 40 g / m 2 The wet nonwoven fabric was then placed in a hot air dryer at 120°C, treated for 3 minutes, air-cooled, and then heat-pressed at 200°C and 1.5 MPa for 3 minutes using a flat plate hot press.

[0136] Table 1 shows the evaluation results of the obtained binder fibers and nonwoven fabrics.

[0137] [Examples 2 and 3]

[0138] Except for changing the number of islands of the sea-island type composite die, polyphenylene sulfide fibers and nonwoven fabrics for binders were obtained in the same manner as in Example 1. Table 1 shows the evaluation results of the obtained binder fibers and nonwoven fabrics.

[0139] [Example 4]

[0140] Polyphenylene sulfide fibers for binder and nonwoven fabric were obtained in the same manner as in Example 1 except that short fibers with an average fiber length of 2.5 mm were obtained when the island-in-sea composite fibers were cut with a shearing machine.

[0141] [Comparative Example 1]

[0142] A nonwoven fabric was obtained in the same manner as in Example 1 except that the undrawn fiber obtained in Reference Example 1 was used as a binder fiber without drawing. The evaluation results of the obtained binder fiber and nonwoven fabric are shown in Table 1.

[0143] [Comparative Example 2]

[0144] Polyphenylene sulfide fibers for binder and nonwoven fabrics were obtained in the same manner as in Example 1, except that the unstretched fibers having a sea-island composite cross section obtained by the method of Example 1 were stretched to 3.0 times between rolls heated to 90° C. and then heat-set using rolls heated to 200° C. The evaluation results of the obtained binder fibers and nonwoven fabrics are shown in Table 1.

[0145] [Example 5, Comparative Example 3]

[0146] Ultrafine polyphenylene sulfide fibers and nonwoven fabrics were obtained in the same manner as in Example 1 except that the temperature of the alkaline aqueous solution in the dissolution treatment of the short fibers of the island-in-sea composite fibers was changed to 70°C (Example 5) and 90°C (Comparative Example 3). The evaluation results of the obtained binder fibers and nonwoven fabrics are shown in Table 1.

[0147] [Example 6]

[0148] A polyphenylene sulfide fiber for binder and a nonwoven fabric were obtained in the same manner as in Example 3, except that the shape of the island component of the sea-island composite fiber was set to a Y-shaped shape and the fiber cross section of the polyphenylene sulfide fiber after the sea component was dissolved was set to a Y-shaped cross section with a non-shapedness of 1.7. The evaluation results of the obtained binder fiber and nonwoven fabric are shown in Table 1.

[0149] [Example 7]

[0150] Polyphenylene sulfide fibers for use as an adhesive and a nonwoven fabric were obtained in the same manner as in Example 3, except that the shape of the island component of the sea-island type composite fiber was made flat, and the fiber cross section of the polyphenylene sulfide fiber after the sea component was dissolved was made a flat cross section with a non-shaped degree of 3.8. The evaluation results of the obtained adhesive fiber and nonwoven fabric are shown in Table 1.

[0151] Table 1

[0152]

[0153] [Examples 8 and 9]

[0154] In addition to changing the unit area weight of the non-woven fabric to 10g / m 2 (Example 8) and 5g / m 2 Except for (Example 9), ultrafine polyphenylene sulfide fibers and nonwoven fabrics were obtained in the same manner as in Example 1. Table 2 shows the evaluation results of the obtained binder fibers and nonwoven fabrics.

[0155] Table 2

[0156]

[0157] It can be seen from Examples 1 to 9 that since the average fiber diameter is small and the crystallinity is low, the nonwoven fabric can be made thinner and the adhesiveness and quality are good.

[0158] On the other hand, in Comparative Example 1, the nonwoven fabric is thick due to the large fiber diameter, and in Comparative Examples 2 and 3, the strength and strength per unit area weight of the nonwoven fabric are low due to the low adhesiveness of the binder fiber, and the quality is also poor.

[0159] Description of the accompanying drawings

[0160] 1: Profile of fiber cross section

[0161] 2: Minimum circumscribed circle

[0162] 3: Maximum inscribed circle

Claims

1. An ultrafine polyphenylene sulfide fiber having an average fiber diameter of 0.2 μm or more and 5.0 μm or less and a crystallinity of 0% or more and 15% or less as calculated by differential scanning calorimetry.

2. The ultrafine polyphenylene sulfide fiber according to claim 1, wherein The ultrafine polyphenylene sulfide fiber is a fiber with a profiled cross section, and the profile degree defined by the following formula is 1.2 or more. Degree of irregularity = minimum circumscribed circle diameter / maximum inscribed circle diameter Here, the minimum circumscribed circle diameter is the diameter of the smallest circle that includes the entire fiber cross section, and the maximum inscribed circle diameter is the diameter of the largest circle that falls within the fiber cross section. Both diameters are measured in μm.

3. The ultrafine polyphenylene sulfide fiber according to claim 1 or 2, wherein The average fiber length is 0.1 mm or more and 6.0 mm or less.

4. A nonwoven fabric comprising the ultrafine polyphenylene sulfide fibers according to claim 1.

5. A method for producing ultra-fine polyphenylene sulfide fibers, An undrawn fiber having a sea-island type composite cross-section in which polyphenylene sulfide is blended in the island component is subjected to removal of the sea component in an alkaline aqueous solution below 70°C, thereby obtaining a fiber having an average fiber diameter of 0.2 μm to 5.0 μm and a crystallinity of 0% to 15% as calculated by differential scanning calorimetry. A method for producing a nonwoven fabric, comprising mixing the ultrafine polyphenylene sulfide fibers according to claim 1 or 2 and drawn polyphenylene sulfide fibers in a papermaking dispersion to make paper, and then subjecting the mixture to thermocompression bonding at a temperature of 130° C. to 250° C.

Citation Information

Patent Citations

  • Method for producing polyphenylene sulfide fiber for papermaking

    JP2010174400A

  • Ultrafine fiber nonwoven fabric and method for producing the same

    JP2010216042A

  • Composite spinneret, method for producing multilayer laminate fiber using the same, and multilayer laminate fiber

    JP2016188454A

  • Wet type nonwoven fabric including polyphenylene sulfide fiber

    JP2020066818A

  • Non-woven fabric, laminated non-woven fabric structure, and filter cloth for filter

    JP2020172729A